The crayon man : the true story of the invention of Crayola crayons - Biebow, Natascha (Houghton Mifflin Harcourt, 2019)
"Celebrating the inventor of the Crayola crayon! This gloriously illustrated picture book biography tells the inspiring story of Edwin Binney, the inventor of one of the world's most beloved toys. A perfect fit among favorites like The Day the Crayons Quit and Balloons Over Broadway"--